Potential Arrhythmogenic Role of TRPC Channels and Store-Operated Calcium Entry Mechanism in Mouse Ventricular Myocytes - Wen, Hairuo; Zhao, Zhenghang; Fefelova, Nadezhda; Xie, Lai-Hua (Frontiers in Physiology, 2018)
BACKGROUND AND PURPOSE Store-operated calcium entry (SOCE) is an important physiological phenomenon that extensively mediates intracellular calcium ion (Cai2+) load. It has been previously found in myocytes isolated from neonatal or diseased hearts. We aimed to determine its existence, molecular nature in undiseased hearts and its potential arrhythmogenic implications under hyperactive conditions. EXPERIMENTAL APPROACH Ventricular myocytes isolated from adult FVB mice were studied by using Cai2+ imaging and whole-cell perforated patch-clamp recording. In addition, lead II ECGs were recorded in isolated Langendorff-perfused mice hearts. Functional TRPC channel antibodies and inhibitors, and TRPC6 activator hyperforin were used. KEY RESULTS In this study, we demonstrate the existence and contribution of SOCE in normal adult mouse cardiac myocytes. For an apparent SOCE activation, complete depletion of sarcoplasmic reticulum (SR) Ca2+ by employing both caffeine (10 mM) and thapsigargin (1 µM) or cyclopiazonic acid (10 µM) was required. Consistent with the notion that SOCE may be mediated by heteromultimeric TRPC channels, SOCEs observed from those myocytes were significantly reduced by the pretreatment with anti-TRPC1, 3, and 6 antibodies as well as by gadolinium, a non-selective TRPC channel blocker. In addition, we showed that SOCE may regulate spontaneous SR Ca2+ release, Cai2+ waves, and triggered activities which may manifest cardiac arrhythmias. Since the spontaneous depolarization in membrane potential preceded the elevation of intracellular Ca2+, an inward membrane current presumably via TRPC channels was considers as the predominant cause of cellular arrhythmias. The selective TRPC6 activator hyperforin (0.1-10 µM) significantly facilitated the SOCE, SOCE-mediated inward current, and calcium load in the ventricular myocytes. ECG recording further demonstrated the proarrhythmic effects of hyperforin in ex-vivo mouse hearts. CONCLUSIONS AND IMPLICATIONS We suggest that SOCE, which is at least partially mediated by TRPC channels, exists in adult mouse ventricular myocytes. TRPC channels and SOCE mechanism may be involved in cardiac arrhythmogenesis via promotion of spontaneous Cai2+ waves and triggered activities under hyperactivated conditions.